Time-Optimal Control of Infinite Order Distributed Parabolic Systems Involving Multiple Time-Varying Lags. (1st September 2016) - Bahaa, G. M.; Kotarski, W.
ABSTRACT: In this article, a time-optimal control problem for linear infinite order distributed parabolic systems involving multiple time-varying lags appearing both in the state equation and in the boundary condition is presented. Some particular properties of the optimal control are discussed.